2022
DOI: 10.3390/vetsci9100573
|View full text |Cite
|
Sign up to set email alerts
|

Honey Bee Pathogen Prevalence and Interactions within the Marmara Region of Turkey

Abstract: Beekeeping has yet to reach its full potential in terms of productivity in Turkey where it has a relatively large role in the economy. Poor colony health is suspected to be the reason for this, but comprehensive disease monitoring programs are lacking to support this notion. We sampled a total of 115 colonies across five different apiaries throughout the Marmara region of Turkey and screened for all of the major bee pathogens using PCR and RNA-seq methods. We found that Varroa mites are more prevalent in compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Furthermore, larvae without Varroa mites were found to have significantly lower HSP70 gene expression levels [ 64 ]; however, in pupae, Varroa mite infestation caused a decrease in HSP70 gene expression [ 65 ]. Varroa is known to vector virulent viruses, including fungal diseases such as stone brood, feed on fat body and hemolymph, as well as suppress the immune system [ 32 , 33 , 48 , 66 ] and, thus, is a major factor in the decline of bee health. Ongoing changes to climate could further augment the stresses caused by this parasitic mite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, larvae without Varroa mites were found to have significantly lower HSP70 gene expression levels [ 64 ]; however, in pupae, Varroa mite infestation caused a decrease in HSP70 gene expression [ 65 ]. Varroa is known to vector virulent viruses, including fungal diseases such as stone brood, feed on fat body and hemolymph, as well as suppress the immune system [ 32 , 33 , 48 , 66 ] and, thus, is a major factor in the decline of bee health. Ongoing changes to climate could further augment the stresses caused by this parasitic mite.…”
Section: Discussionmentioning
confidence: 99%
“…All primer set sequence information used for gene expression analysis can be found in Table S1 . Methods for the RNA extraction of other gene expression analyses were adapted from [ 48 ]. Briefly, a 5 mm steel bead was added to 200 µL of the bee homogenate in a 2 mL Eppendorf safe-lock microcentrifuge tube.…”
Section: Methodsmentioning
confidence: 99%
“…This result corresponds to its high prevalence and occurrence worldwide (Beaurepaire et al, 2020). Studies in neighboring countries found a prevalence of 29% in Syria (Abou Kubaa et al, 2018), 70% in Egypt (Kandel et al, 2023) and 100 % in Turkey (Mayack and Hakanoğlu, 2022). BQCV is currently considered a benign viral pathogen of adult honey bees, possibly because its mode of horizontal transmission is primarily direct by food exchange among nestmates which does promote high virus replication (Al Naggar and Paxton, 2020).…”
Section: Fig (1): Prevalence Of Viruses In Palestinian Honey Bee Colo...mentioning
confidence: 99%
“…It was initially discovered in honey bees by specific PCR in 28 of 197 time-course samples in Mississippi and South Dakota (USA) mainly in July (Runckel et al, 2011). As yet a second study from Turkey only reported minute amounts of virus RNA in worker bees by RNA-seq reads (Mayack and Hakanoğlu, 2022). The biology of the virus and its potential pathogenicity and transmission is not yet known, BSRV appears to be a multi-host pathogen having been also detected by metagenomics analyses in mosquitoes and soybean and maize (Feng et al, 2017, Shi et al, 2015and Wamonje et al, 2017.…”
Section: Fig (1): Prevalence Of Viruses In Palestinian Honey Bee Colo...mentioning
confidence: 99%
See 1 more Smart Citation